Rekayasa Growth Light LED Berbasis Solar Cell untuk Percepatan Pertumbuhan Tanaman Hidroponik Pada Usaha “Sidomulyo Hidroponik” - Rafil Arizona; Jhonni Rahman; Syarifah Farradina; Zaflis Zaim; Prima Titisari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity is a research-based community service program. The goal of this community service program is to create a series of solar cell-based grow light led lights as a source of electrical energy in the "Sidomulyo Hydroponics" business, to increase the growth of hydroponic plants, to improve the quality and quantity of hydroponic plants, to provide residents with insight into optimizing the use of public land for urban farming, and to improve mental health during the pandemic by growing hydroponic crops. This program's outputs include the development of skills for residents of Sidomulyo housing to cultivate hydroponically, as well as the establishment of a hydroponic plant center. The implementation method used consists of two major stages: preparation and core. The following are the implementation results: all sessions in the preparation stage, as well as the core program of socialization, inauguration, core activities, and design projects, were completed on time. The use of a series of solar cell-based LED grow lights as a source of hydroponic electrical energy, increasing the quality and quantity of hydroponic plants in the "Sidomulyo Hydroponics" business, and being able to practice self-healing are all indicators of success.